PEDAGOGICAL CONDITIONS FOR DEVELOPING THE CREATIVE THINKING OF FUTURE FINE ARTS TEACHERS THROUGH MINIATURE COMPOSITION (Multidisciplinary Journal of Science and Technology, 2026)
This article provides a comprehensive theoretical and practical analysis of developing creative thinking in future fine arts teachers through the lens of miniature composition. The study explores the psychological and pedagogical essence of creativity, its structural components, and the unique didactic potential of Oriental miniature art. A systematic framework of pedagogical conditions—including creative environment modeling, integrative approaches, and problem-based learning—is proposed to enhance students' artistic and professional competencies. The findings emphasize that integrating miniature composition into the curriculum not only preserves cultural heritage but also fosters innovative visual problem-solving skills in future educators.